(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2018)
Purpose: We prospectively evaluated the surgical outcomes of non ligation of hernial sac technique in children with a palpable undescended testis compared with the traditional hernial sac ligation technique during orchiopexy. Material and Methods: A total of 34 orchiopexies (30 children with age ranged from 6 months to 5 years) were included and randomly assigned to the non ligation of hernial sac technique orchiopexy group (Group-A, 15 children, 16 testes) and the traditional hernial sac ligation orchiopexy group (Group-B, 15 children, 18 testes). Operation time and surgical complications were compared between the two groups. Complications, testicular location and development of inguinal hernia were assessed at the follow-up evaluation for 6 months postoperatively. Results: The operation time was significantly shorter in Group-A (34.13±10.3 minutes) than Group-B (73.73±28.97 minutes) (<p001). Postoperative complications were found in two cases (wound infection and testicular re-ascent) in Group-B. Wound infection was managed by conservative care and redo surgery was done for testicular re-ascent after 6 months of operation. None of the patients developed post operative inguinal hernia. Conclusion: We conclude that non ligation of hernial sac technique is a simple procedure that is associated with a shorter operation time than the conventional hernial sac ligation technique during open orchiopexy for palpable undescended testis. Journal of Paediatric Surgeons of Bangladesh (2016) Vol. 7 (2): 35-40